2016
DOI: 10.1016/j.ajpath.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Local Glucocorticoid Activation by 11β-Hydroxysteroid Dehydrogenase 1 in Keratinocytes

Abstract: Over the past decade, extra-adrenal cortisol production was reported in various tissues. The enzyme that catalyzes the conversion of hormonally inactive cortisone into active cortisol in cells is 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1). We recently reported that 11β-HSD1 is also expressed in keratinocytes and regulates inflammation and keratinocyte proliferation. To investigate the function of 11β-HSD1 in keratinocytes during inflammation in vivo, we created keratinocyte-specific 11β-HSD1 knockout (K5-Hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
5
21
0
Order By: Relevance
“…In contrast, silencing of HSD11B2 leads to elevation of cortisol levels (Cirillo and Prime, 2011) demonstrating that the relative levels and activities of these two enzymes determine the overall levels of glucocorticoids locally present in the skin (Cirillo and Prime, 2011; Tiganescu et al , 2011). In psoriatic skin, the mRNA expression of both HSD11B1 , consistent with findings from a recent study (Terao et al , 2016), and HSD11B2 is decreased, but the ratio between these two enzymes is biased toward greater suppression of HSD11B1 and therefore less production of cortisol. This is similar to what we observe in several other skin diseases and wound healing (Supplementary file 4).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, silencing of HSD11B2 leads to elevation of cortisol levels (Cirillo and Prime, 2011) demonstrating that the relative levels and activities of these two enzymes determine the overall levels of glucocorticoids locally present in the skin (Cirillo and Prime, 2011; Tiganescu et al , 2011). In psoriatic skin, the mRNA expression of both HSD11B1 , consistent with findings from a recent study (Terao et al , 2016), and HSD11B2 is decreased, but the ratio between these two enzymes is biased toward greater suppression of HSD11B1 and therefore less production of cortisol. This is similar to what we observe in several other skin diseases and wound healing (Supplementary file 4).…”
Section: Discussionsupporting
confidence: 89%
“…GC, glucocorticoid; NHEK, normal human keratinocyte; RT-qPCR, quantitative real-time PCR; WT, wild type. local stress regulatory system is disrupted in Hsd11b1 KCe/e epidermis (Terao et al, 2016). Therefore, we hypothesized that disruption of the local stress regulatory system in skin could contribute to alloknesis as part of a compensatory hostdefense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocyte-specific Hsd11b1 KCe/e mice were generated as described previously (Terao et al, 2016). Briefly, Krt5-Cre þ/þ transgenic and Hsd11b1 flox/flox mice were maintained on a C57BL6/J background and interbred to generate mice that carried Krt5-Cre transgene and a floxed Hsd11b1 allele (Krt5-Cre þ/e Hsd11b1 flox/e ).…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…These properties, as well as the relative long life of a keratinocyte compared with other inflammatory cells such as the neutrophil or eosinophil, make the keratinocyte a potentially important player in the amplification and persistence of inflammatory and immune responses in AD. Several groups have reported that GC exhibits anti-inflammatory eff ;ects in keratinocytes treated with TNFα [32,33], hapten [34], UV-B irradiation [35], IFNg [36], and induces keratinocyte terminal differentiation [37]. However, few investigations have been conducted to determine whether SEB contributes to the resistance to GCs through keratinocytes.…”
Section: Discussionmentioning
confidence: 99%